Trajetória do serviço social escolar de Limeira: construção de uma educação para além do capital - Bull, Thalita Giovanna (2010)
This essay seeks to show the working process of social workers in the sector of School Social Work, including the historical path by which these professionals achieved the Municipal Department of Education and have started to build an experience that has gained recognition and visibility. Based in an interview with the coordinator of the department, which followed this process from the beginning, we reconstruct this path by identifying the way in which the determinations have affected it. Through the application of a questionnaire we draw a profile on the main personal and professional characteristics of social workers in the team. We have presented the tasks of social workers in this sector as well as the major projects conducted during the 13 years in which this experience has been built. Based on the theoretical framework supported by authors from the Marxist tradition field, particularly in the specific context of Social Work, as well as professional experience in the industry built School of Social Work, this researcher considers education an important field of disputes on hegemony, where social workers can and should contribute to build a working class culture, which allows a break with the forms of domination and exploitation present in the capitalist society, to build an "education beyond the capital". (MÉSZÁROS, 2005)